Mistranslations of Film Titles: Between Fidelity and Advertising - Surdyk, Augustyn; Urban, Anna (Wydawnictwo Naukowe UAM, 2016)
In the paper, the authors present and analyse examples of mistranslated film titles into the Polish language, selected from a database of over 1,100 titles and presented on the sample of the film genre comedy with all its subgenres. The authors discuss various film title translation strategies and procedures with reference to the literature on the subject. In the conclusions, the authors attempt to explain the reasons for the selection of certain translation procedures, with special focus on the free formulation of titles as the least transparent.
Keywords: film titles; translation procedures; mistranslation; fidelity in translation